A door to the unknown: crossing boundaries through picturebook art - Katarzyna Smyczyńska (Problemy Wczesnej Edukacji)
This paper engages with the question of the ethical implications of, and artistic imagination in picturebooks. The analysis relies on two visual narratives confronting the theme of cultural difference. The juxtaposition of the two books that share the themes of visiting and hosting, of confronting otherness, and of cultural prejudice indicates differences in their narrative and artistic potential. The analysis of formal strategies in Jemmy Button by Jennifer Uman and Valerio Vidali and in Eric by Shaun Tan serves to point out the role of artistic imagination and narrative wisdom in creating visual literature.